Comparison of phantom materials for use in quality assurance of microbeam radiation therapy. (18th May 2017) - Cameron, Matthew; Cornelius, Iwan; Cutajar, Dean; Davis, Jeremy; Rosenfeld, Anatoly; Lerch, Michael; Guatelli, Susanna
Abstract : Solid phantoms that are routinely used in quality assurance (QA) of conventional megavoltage X‐ray beam radiation therapy may not be designed for use in synchrotron‐based microbeam radiation therapy (MRT). This work quantitatively determines the most appropriate solid phantom to use in dosimetric MRT QA using Geant4 ‐based Monte Carlo simulations. Abstract : Microbeam radiation therapy (MRT) is a promising radiotherapy modality that uses arrays of spatially fractionated micrometre‐sized beams of synchrotron radiation to irradiate tumours. Routine dosimetry quality assurance (QA) prior to treatment is necessary to identify any changes in beam condition from the treatment plan, and is undertaken using solid homogeneous phantoms. Solid phantoms are designed for, and routinely used in, megavoltage X‐ray beam radiation therapy. These solid phantoms are not necessarily designed to be water‐equivalent at low X‐ray energies, and therefore may not be suitable for MRT QA. This work quantitatively determines the most appropriate solid phantom to use in dosimetric MRT QA. Simulated dose profiles of various phantom materials were compared with those calculated in water under the same conditions. The phantoms under consideration were RMI457 Solid Water (Gammex‐RMI, Middleton, WI, USA), Plastic Water (CIRS, Norfolk, VA, USA), Plastic Water DT (CIRS, Norfolk, VA, USA), PAGAT (CIRS, Norfolk, VA, USA), RW3 Solid Phantom (PTW Freiburg, Freiburg, Germany), PMMA, Virtual Water (Med‐Cal, Verona, WI, USA) and Perspex. RMI457 Solid Water and Virtual Water were found to be the best approximations for water in MRT dosimetry (within ±3% deviation in peak and 6% in valley). RW3 and Plastic Water DT approximate the relative dose distribution in water (within ±3% deviation in the peak and 5% in the valley). PAGAT, PMMA, Perspex and Plastic Water are not recommended to be used as phantoms for MRT QA, due to dosimetric discrepancies greater than 5%.